2015
DOI: 10.1080/01635581.2015.1062118
|View full text |Cite
|
Sign up to set email alerts
|

Oral Nucleotides Only Minimally Improve 5-Fluorouracil-Induced Mucositis in Rats

Abstract: Chemotherapy-induced mucositis is characterized by inflammation and ulceration of the intestinal mucosa, compromising intestinal function. Exogenous nucleotides have been reported to repair the mucosa. The nucleotide preparation, Nucleoforce F0328 (Nucleoforce), was investigated for its potential to ameliorate intestinal mucositis in rats. Female Dark Agouti rats (n = 8/group) were gavaged once daily with Nucleoforce (175 mg/kg) or water from Days 0 to 8 and injected (i.p.) with 5-fluorouracil (5-FU; 150 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…Decreased intestinal length may aid in maintaining mucosal integrity to protect against translocation of pathogens into the submucosa 7,12 . Furthermore, 5-FU resulted in decreased thymus and spleen weights, similar to previous studies using 5-FU 14,17,18,42 .…”
Section: Discussionsupporting
confidence: 88%
“…Decreased intestinal length may aid in maintaining mucosal integrity to protect against translocation of pathogens into the submucosa 7,12 . Furthermore, 5-FU resulted in decreased thymus and spleen weights, similar to previous studies using 5-FU 14,17,18,42 .…”
Section: Discussionsupporting
confidence: 88%
“…This is presumably due to the increased cell-turnover rate which is a characteristic feature of the small intestine[ 3 ]. The main histological findings of villus shortening and crypt disruption caused by 5-FU administration were typical, and in concordance with other studies[ 27 - 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…Patient symptoms arising as a result of the barrage of pathophysiological changes occurring in the alimentary tract in mucositis typically include reduced food consumption, and hence body weight decrease[ 29 , 31 ]. Clinical features in the current study were classic although we observed increased urine output in the absence of polydipsia.…”
Section: Discussionmentioning
confidence: 99%
“…The weight loss and increased intestinal MPO expression following 5-FU administration confirmed that this model induced gut toxicity in rats. In accordance with the previous works from which these tissues were scavenged, acute intestinal inflammation was identified by significant increases in jejunal and ileal MPO expression following 5-FU administration (see the following published works for other phenotypic and characteristic parameters studied (Mashtoub et al, 2013(Mashtoub et al, , 2015Wang et al, 2017)). CAR administration was associated with attenuated acute intestinal inflammation in the jejunal and ileal regions of rats with 5IGT.…”
Section: Discussionsupporting
confidence: 87%